Loss of immunity‐supported senescence enhances susceptibility to hepatocellular carcinogenesis and progression in Toll‐like receptor 2‐deficient mice12. Issue 1 (7th January 2013) - Lin, Heng; Yan, Jun; Wang, Ziyan; Hua, Fang; Yu, Jiaojiao; Sun, Wei; Li, Ke; Liu, Hong; Yang, Hongzhen; Lv, Qi; Xue, Jianfei; Hu, Zhuo‐Wei
Abstract Hepatocellular carcinoma (HCC) is a complication at the endstage of chronic inflammatory liver diseases with dismal prognosis. Targeting of Toll‐like receptor (TLR) 2 attenuates tumor metastases; we hypothesized that blocking TLR2 might also play a crucial role in reducing hepatocarcinogenesis. Surprisingly, we found that the genetic deletion of TLR2 increased susceptibility to diethylnitrosamine (DEN), a genotoxic carcinogen that can induce HCC. Indeed, TLR2‐deficient mice showed a significant increase in carcinogenesis and progression of HCC as indicated by increases in tumor nodule size, tumor volume, and animal death. The enhanced susceptibility to DEN‐induced HCC was associated with a broad‐spectrum reduction in the immune response to DEN‐induced liver injury. We found that TLR2 deficiency caused a decrease in the infiltration of macrophages and an attenuation of apoptosis signal regulating kinase 1 (ASK1) / p38 mitogen‐activated protein kinase (p38 MAPK) / nuclear factor kappa B (NF‐κB) signaling, which led to a decrease in the expression of interferon‐gamma (IFN‐γ), tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐1α/β, IL‐6, and Cxcl‐2 as well as suppression of autophagy flux and increases in oxidative stress and p62 aggregation in liver tissue. The defects in immune networks resulted in suppressed p21‐ and p16/pRb‐dependent senescence, which caused an increase in proliferation and a decrease in apoptotic and autophagy‐associated cell death in mouse livers. Restoring cellular senescence and autophagy flux by treating TLR2‐deficient mice with IFN‐γ, a T helper 1 (Th1) cytokine and positive modulator of senescence and autophagy, could attenuate the carcinogenesis and progression of HCC associated with TLR2‐deficient animals. Conclusion: The loss of immune networks supporting cellular senescence and autophagy flux is attributed to enhanced susceptibility to DEN‐induced hepatocellular carcinogenesis and progression in TLR2‐deficient mice. These findings may be used to prevent the development of liver cancer. (HEPATOLOGY 2013)